The application of lognormal distribution on the new two-sided group chain sampling plan - Muhammad Farouk,; Nazrina Aziz,; Zakiyah Zain, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This paper gives emphasis on the technical aspect of acceptance criteria in acceptance sampling plans, more specifically the family of two-sided group chain sampling plans. The new two-sided complete group chain sampling plan (NTSCoGCh) operates with five acceptance criteria, while the two-sided group chain sampling plan (TS-GCh) operates with three acceptance criteria. Generally, the number of acceptance criteria has a direct influence on the probability of lot acceptance; the more criteria being accepted leads to higher probability of lot acceptance. This paper suggests a new, balanced plan for the family of two-sided group chain sampling plans. The plan, named the new two-sided group chain sampling plan (NTSGCh), operates with four acceptance criteria. The Lognormal distribution is used to represent the production sequence of manufactured products in this study. A time truncated life test simulation is carried out to obtain the minimum number of groups required and the probability of lot acceptance. The findings show that the NTSGCh outperformed its predecessors. In conclusion, the NTSGCh is a viable alternative for implementation in the industry.